Long-Term Implementation of Strategic Management and Increasing The Function of School Committees to Promote Environmental Education - Rifqi, Ainur; Bafadal, Ibrahim; Arifin, Imron; Supriyanto, Achmad (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2024)
Environmental education is one of the keys to people, especially students, having an awareness of protecting the environment. This qualitative study aims to investigate the best ways for school committees to play a role and how to adopt strategic management for environmental education to be sustained over the long term. The research subjects comprised one principal, five teachers, five students, and three school committee members. Data were collected through interviews, observations, and literature studies related to the strategic planning process and the role of school committees. The findings demonstrated that schools had to adopt a strategic management approach to accomplish environmental education goals, including formulation, implementation, assessment, and control. The first four years of school focused on implementing environmental education in school. For the next four years, the focus shifts to civilizing the environment within the school's internal environment. In the third four years, the school concentrates on acculturating the external environment. The school committee plays a vital role in implementing environmental education by considering school regulations, supervising, supporting schools financially, and actively participating in the process. This research implies that this research can be a basis for further research, especially in strategic planning and school committees.